First report on the herpetofauna of Ataúro Island, Timor Leste - Hinrich Kaiser; Caitlin Sanchez; Scott Heacox; Andrew Kathriner; Agivedo Ribeiro; Zito Soares; Luis Araujo; Sven Mecke; Mark O’Shea (Check List, 2013)
We describe for the first time the terrestrial herpetofauna of Ataúro Island, Timor-Leste, a small mountainous island in the Inner Banda Arc of the Lesser Sunda Archipelago. The island supports a fauna of ten lizard species in three families (Gekkonidae, n = 5; Scincidae, n = 4; Varanidae, n = 1) and four snake species in three families (Colubridae, n = 3; Typhlopidae, n = 1; Viperidae, n = 1). In addition to a set of lizards (e.g., Cryptoblepharus, Eutropis, Gehyra, Gekko, Hemidactylus, Lamprolepis) and snakes (e.g., Lycodon, Ramphotyphlops, Trimeresurus) typical for the Lesser Sunda Islands, there appear to be undescribed endemic species of Cyrtodactylus, Eremiascincus, and Varanus on Ataúro. Our surveys to date have not revealed the presence of any amphibians, turtles, or crocodiles.